Carbazole-containing amides and ureas: Discovery of cryptochrome modulators as antihyperglycemic agents. Issue 3 (1st February 2018) - Humphries, Paul S.; Bersot, Ross; Kincaid, John; Mabery, Eric; McCluskie, Kerryn; Park, Timothy; Renner, Travis; Riegler, Erin; Steinfeld, Tod; Turtle, Eric D.; Wei, Zhi-Liang; Willis, Erik
Graphical abstract: Abstract: A series of novel carbazole-containing amides and ureas were synthesized. A structure–activity relationship study of these compounds led to the identification of potent cryptochrome modulators. Based on the desired pharmacokinetic/pharmacodynamic parameters and the results of efficacy studies in db/db mice, compound50 was selected for further profiling.